HUBUNGAN KONSUMSI SUPLEMEN TABLET FE DENGAN KEBUGARAN JASMANI (Studi pada Siswi di SMA Negeri 15 Semarang) - Kurnia Sari Ramadhon; M. Zen Rahfiluddin; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2020)
ABSTRACT Adolescent girls who experience anemia increases from 37.1% to 48.9% in 2018. To overcome anemia in adolescent girls can be done by paying attention to food intake consumed and increasing efforts so that iron is less biased sufficient every day. The impact of iron deficiency anemia in adolescents is to reduce immunity, reduce concentration of learning and can experience premature births, bleeding and abortion during pregnancy. Iron can help the process of formation of blood hemoglobin in order to facilitate O2 throughout the body, so iron (Fe) can play a role in improving physical fitness. The purpose of this study was to determine the relationship of consumption of Fe tablet supplementation with physical fitness in young women in SMA Negeri 15 Semarang. This type of research is descriptive analytic with cross sectional approach. The population of class XI adolescent girls is 214, the sampling technique uses the purposive sampling method. Samples taken as many as 67 students. The research instruments were screening questionnaire, research questionnaire, 24-hour food consumption recall and physical fitness test (using Harvard Step Test). Data analysis using the Kolmogorov-Smirnov test and difFerent tests using the Spearman Rank test. The results showed that most respondents aged 16 years were 86.6%. There was no relationship between consumption of Fe tablets with physical fitness of girls (p = 0.165), protein adequacy level with physical fitness of girls (p = 0.304) and iron intake (p = 0.291), vitamin B12 intake (p = 0.096), intake of vitamin C (p = 0.102) with physical fitness of young women. Suggestions for schools need a routine ongoing program to improve physical activity and the provision of monitoring cards for consumption of Fe tablets so that they can help improve the fitness of students in the school environment. Keyword : Adolescent Girls, Physical Fitness, Compliance, Iron TabletSupplement